Influence of age and gender on salivary flow rate in completely edentulous patients (Mustansiria Dental Journal, 2018)
The denture retention and stability are dependent on saliva flow rate and quality,patients with dry mouth may have problems with the stability or comfort of maxillarycomplete dentures.Dry mouth is a common feature in the elderly, but is not clear what proportion ofincidences is related to functional disturbances and whether age persue and Genderplay a role. The aim of this study is to determine the effect of age on unstimulated(Resting) whole and stimulated saliva flow rates. It was determined in 100unmedicated, healthy individuals wearing complete dentures. The subjects weredivided into two age groups: group A(< 70 years), group B(> 70 years). A significantdecrease in the secretion rates of unstimulated whole saliva in relation to age wasobserved in the study population (p< 0.001).Females had significantly lower mean flow rates than males for unstimulated(resting) whole saliva.